Pengaruh Perendaman Benih Pada Berbagai Suhu Awal Air Terhadap Viabilitas Benih Kayu Afrika (Maesopsis Eminii) - Oben Oben; Afif Bintoro; Melya Riniarti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
One of the propagation problems in generative of umbrella tree was seed dormancy. To break the seed dormancy of umbrella tree seed, soaking at different initial temperatures of water was used. The objectives of this research were to find out the effect of initial temperature treatment to the germination percentage, the germination speed rate, and the ability to germinate, and also to find the optimum initial temperature for umbrella tree germination. The research has started February until May 2012 in PT. Anugerah Subur Sejahtera, Ulak Bandung Village, sub-districtofMuara Sahung, Kaur Regency, Bengkulu.This research used completely randomized design (CRD) with 4 treatment and 3 replications, each series of experiments used 100 seeds. The result shown that soaking treatment at different initial temperature of water has been significantly affected the germination percentage, and the umbrella tree seed without soaking gave the best result. Keywords: germination, scarification, seed viability, umbrella tree